2011
DOI: 10.4028/www.scientific.net/amr.366.518
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Ions Penetration Resistance of New-Old Concrete

Abstract: By use of ASTM C1202, this paper studied the influence of mineral admixtures on the chloride ions penetration resistance of the new-old concrete compound system. The results indicate that the performance of new-old concrete exert significant influence on the new-old concrete compound system. The addition of mineral admixtures improve the permeability properties of new-old concrete. Adding fly ash(FA) require a relatively longer time to get its beneficial effect. When 30% weight of cement is replaced by 10% FA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Zong researched the utilization of compound admixtures in the construction of frozen mine shaft lining concrete, providing data for optimizing the mix proportion of concrete admixture content [ 7 ]. He et al employed ASTM C1202 to investigate the effects of mineral admixtures on the resistance of chloride ions penetration in the new concrete compound system [ 8 ]. Li et al employed ring-test methods to study the early-age cracking characteristics of compound mineral admixture concrete, incorporating steel slag, blast furnace slag, and fly ash [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zong researched the utilization of compound admixtures in the construction of frozen mine shaft lining concrete, providing data for optimizing the mix proportion of concrete admixture content [ 7 ]. He et al employed ASTM C1202 to investigate the effects of mineral admixtures on the resistance of chloride ions penetration in the new concrete compound system [ 8 ]. Li et al employed ring-test methods to study the early-age cracking characteristics of compound mineral admixture concrete, incorporating steel slag, blast furnace slag, and fly ash [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another important issue in wet connection joints is interface treatment. Many studies had found that the interface treatment has a significant impact on the mechanical properties of the interface, such as bonding, 11,12 shearing 13 and bending, 14 as well as durability properties such as permeability and chloride ingress resistance 15–17 . According to the mesoscopic composition, the concrete can be regarded as a two‐phase combination of aggregate and mortar 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies had found that the interface treatment has a significant impact on the mechanical properties of the interface, such as bonding, 11,12 shearing 13 and bending, 14 as well as durability properties such as permeability and chloride ingress resistance. [15][16][17] According to the mesoscopic composition, the concrete can be regarded as a two-phase combination of aggregate and mortar. 18 The mechanical properties and durability of concrete largely depend on the characteristics of its constituent phases, such as aggregate particle size, aggregate volume fraction, mortar properties, and initial defects.…”
mentioning
confidence: 99%